2020
DOI: 10.4174/astr.2020.98.3.116
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors predicting survival rate over 10 years of patients with intrahepatic cholangiocarcinoma after hepatic resection

Abstract: Hepatic resection is considered as the optimal treatment for intrahepatic cholangiocarcinoma (IHCC); however, the survival rate after resection is low and the analysis of long-term (≥10 years) survivors is rare. This study aims to analyze the clinicopathological factors affecting the long-term survival of patients with IHCC. Methods: Between January 2003 and December 2012, a single-institution cohort of 429 patients who underwent hepatic resection for IHCC were reviewed retrospectively. Surgical results, recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…CA19‐9 has been established as the main serum tumour marker for ICC 26 . Several studies have shown the negative influence of higher CA19‐9 values on survival 27‐30 . Therefore, elevated CA19‐9 values are obviously predictive of poor tumour biology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA19‐9 has been established as the main serum tumour marker for ICC 26 . Several studies have shown the negative influence of higher CA19‐9 values on survival 27‐30 . Therefore, elevated CA19‐9 values are obviously predictive of poor tumour biology.…”
Section: Discussionmentioning
confidence: 99%
“…26 Several studies have shown the negative influence of higher CA19-9 values on survival. [27][28][29][30] Therefore, elevated CA19-9 values are obviously predictive of poor tumour biology. Precise cut-offs for better prediction may be defined in the future.…”
Section: Follow-upmentioning
confidence: 99%
“…Several factors can worsen survival, such as pathogenic factors, tumor size, tumor number, lymph node metastasis (LNM), vascular infiltration, degree of differentiation, and carbohydrate antigen (CA) 19-9 concentration, all of which are related to the ICC prognosis. [4][5][6][7][8][9] LNM is a clear risk factor and is particularly important. [4][5][6]10 Lymph node dissection (LND) is a component of ICC radical surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor size, stage and morphology are associated with prognosis and are all included in the American Joint Committee on Cancer (AJCC) staging system. Surgical margins, local lymph node tumor involvement and vascular or perineural invasion markedly affect survival [12,13]. While there is strong evidence to support the causative role of cirrhosis in the development of iCCA, the role of cirrhosis as a prognostic factor is debatable with contradicting findings from previous studies [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%